Gaze behavior during curb approach: The effect of mobile device use while walking. (September 2016) - Kim, Robyn; Lester, Benjamin D.; Schwark, Jeremy; Cades, David; Hashish, Rami; Moorman, Helene; Young, Douglas
Mobile device use is becoming increasingly prevalent during everyday activities. The simultaneous use of such technology while performing various activities may increase risk of human error and accidents, such as falls. In addition to effects on cognitive and attentional resources, mobile device use may influence visual behavior, thus affecting the user's ability to perceive obstacles in the environment and respond appropriately. The purpose of this study was to examine the influence of texting on gaze behavior during the approach and negotiation of a simulated curb. Wireless eye-tracking was used to record gaze during locomotion, with and without concurrent texting. Semantic Gaze Mapping (SMI, Inc.) was used to co-register participants' gaze to different areas of interest (AOIs). Texting resulted in significant reductions in gaze dwell time on the curb and the number of times the curb was fixated. These findings suggest that mobile device use may have a negative effect on navigation during locomotion by reducing visual attention to task-relevant areas along the future path of travel.